A Simple Method for Estimating the Economic Cost of Productivity Loss Due to Blindness and Moderate to Severe Visual Impairment - Eckert, Kristen A.; Carter, Marissa J.; Lansingh, Van C.; Wilson, David A.; Furtado, João M.; Frick, Kevin D.; Resnikoff, Serge (Ophthalmic epidemiology, 2015)
Purpose: To estimate the annual loss of productivity from blindness and moderate to severe visual impairment (MSVI) using simple models (analogous to how a rapid assessment model relates to a comprehensive model) based on minimum wage (MW) and gross national income (GNI) per capita (US$, 2011). Methods: Cost of blindness (COB) was calculated for the age group ≥50 years in nine sample countries by assuming the loss of current MW and loss of GNI per capita. It was assumed that all individuals work until 65 years old and that half of visual impairment prevalent in the ≥50 years age group is prevalent in the 50-64 years age group. For cost of MSVI (COMSVI), individual wage and GNI loss of 30% was assumed. Results were compared with the values of the uncorrected refractive error (URE) model of productivity loss. Results: COB (MW method) ranged from $0.1 billion in Honduras to $2.5 billion in the United States, and COMSVI ranged from $0.1 billion in Honduras to $5.3 billion in the US. COB (GNI method) ranged from $0.1 million in Honduras to $7.8 billion in the US, and COMSVI ranged from $0.1 billion in Honduras to $16.5 billion in the US. Most GNI method values were near equivalent to those of the URE model. Conclusion: Although most people with blindness and MSVI live in developing countries, the highest productivity losses are in high income countries. The global economy could improve if eye care were made more accessible and more affordable to all.